Left Ventricular Assist Device Implantation with Concomitant Aortic Valve and Ascending Aortic Replacement - Katharina Huenges; Bernd Panholzer; Jochen Cremer; Assad Haneya (Case Reports in Medicine)
Left ventricular assist device (LVAD) is nowadays a routine therapy for patients with advanced heart failure. We present the case of a 74-year-old male patient who was admitted to our center with terminal heart failure in dilated cardiomyopathy and ascending aortic aneurysm with aortic valve regurgitation. The LVAD implantation with simultaneous aortic valve and supracoronary ascending aortic replacement was successfully performed.